Evolutionary dynamics of recurrent hepatocellular carcinoma under divergent immune selection pressures - Chakravarthy, Ankur; Pasini, Elisa; Zhao, Xun; To, Jeffrey; Shen, Shu Yi (Roxana); Fischer, Sandra; Ghanekar, Anand; Vogel, Arndt; Grant, Robert C.; Knox, Jennifer; Sapisochin, Gonzalo; Gores, Gregory J.; et al. (Frontiers in Oncology, 2025)
Hepatocellular carcinoma (HCC) is a highly lethal, aggressive malignancy. Little is known about the evolutionary trajectories of HCC and how clinical decision-making could be informed based on biopsies of the initial tumour. Here, we report the whole-exome sequencing of a unique series of resected HCC tumours and matched recurrences. This cohort included patients who received a liver transplant and who were immunosuppressed at time of recurrence, in comparison to patients who underwent liver resection for HCC and immunocompetent at time of recurrence, therefore facilitating analyses of immune selection in driving evolutionary divergence. We find extensive evolutionary divergence between baseline and recurrent tumours, with the majority of mutations in our cohort being private, in the process informing sampling guidelines for precision oncology in this disease. We also find no evidence that immunosuppression relaxes immune selection pressures, given the absence of a genomic footprint reflecting the presentation of neoantigens or altered dynamics of genomic evolution. We attribute this to the presence of genetic lesions that confer the capabilities of immune evasion in these tumours prior to transplantation, and then validate the link between immune selection pressures and the emergence of these lesions in publicly available HCC datasets. Our findings point to HCC as a cancer with extensive evolutionary divergence over time, partly defined by an irreversible, genetically determined trajectory towards immune escape.